2013
DOI: 10.2174/1871520613666131125123059
|View full text |Cite
|
Sign up to set email alerts
|

Myricetin Induces Apoptosis in HepG2 Cells Through Akt/p70S6K/Bad Signaling and Mitochondrial Apoptotic Pathway

Abstract: The present investigation was undertaken to gain insight into the molecular mechanism by which myricetin induces apoptosis in human hepatocarcinoma HepG2 cells. Myricetin caused the disruption of mitochondrial membrane potential in a dose-dependent manner. Moreover, myricetin triggered translocation of the pro-apoptotic protein Bax to the mitochondria, downregulation of anti-apoptotic Bcl-2 expression and upregulated the expression of pro-apoptotic protein Bad in the mitochondria. The present study also showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 34 publications
5
30
0
1
Order By: Relevance
“…Cell apoptosis signaling pathways classified into the death receptor (extrinsic) pathway and the mitochondrial (intrinsic) pathway . The extrinsic pathways may be triggered by receptor (Fas, TRAIL, DR5, and DR4) and lead to activate caspase‐8 and caspase‐3 for inducing apoptosis or through dysfunction of mitochondria based on the ratio of proapoptotic protein (Bak or BAX)/antiapoptotic protein (Bcl‐2 or Bcl‐xl) to induce apoptosis which called the intrinsic cell apoptotic pathways . In the present study, Figure indicated that ouabain increased the activities of caspase‐8, ‐9, and ‐3, and these effects are in time‐dependently.…”
Section: Discussionsupporting
confidence: 53%
“…Cell apoptosis signaling pathways classified into the death receptor (extrinsic) pathway and the mitochondrial (intrinsic) pathway . The extrinsic pathways may be triggered by receptor (Fas, TRAIL, DR5, and DR4) and lead to activate caspase‐8 and caspase‐3 for inducing apoptosis or through dysfunction of mitochondria based on the ratio of proapoptotic protein (Bak or BAX)/antiapoptotic protein (Bcl‐2 or Bcl‐xl) to induce apoptosis which called the intrinsic cell apoptotic pathways . In the present study, Figure indicated that ouabain increased the activities of caspase‐8, ‐9, and ‐3, and these effects are in time‐dependently.…”
Section: Discussionsupporting
confidence: 53%
“…These results confirm speculation that galangin and myricetin inhibit angiogenesis in OVCAR-3 cells, at least partly, through the Akt/p70S6K/HIF-1α/VEGF pathway. Previous works found that myricetin had effects on the Akt/p70S6K pathway in HepG2 and SKH-1 cells (Jung et al, 2010; Zhang, Chen et al, 2013) and galangin inhibits the phosphorylation of Akt in HepG2 cells (Zhang, Li et al, 2013). This agrees with the results obtained in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have reported that galangin and myricetin inhibited cell growth in several cancer cells, such as hepatoma, pancreatic, esophageal, melanoma, gastric, and colon carcinoma cells (Kim, Jeon, & Nam, 2012; Kim, Ha, Yoon, & Lee, 2014; Phillips, Sangwan, Borja-Cacho, Dudeja, Vickers, & Saluja, 2011; Zang et al, 2014; Zhang et al, 2010; Zhang, Lan, Huang, & Hua, 2013; Zhang, Chen et al, 2013). However, their effects on ovarian cancer cells are currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…AKT can activate BAD by phosphorylation on Ser136 [20] or activate NF-κB via regulating IκB kinase (IKK) [21], thus results in anti-apoptotic effects. AKT pathway also involves in chemoresistance.…”
Section: Discussionmentioning
confidence: 99%